2020
DOI: 10.3347/kjp.2020.58.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Clonorchis sinensis Human Infections in Endemic Areas, Haman-Gun, Republic of Korea: A Case-Control Study

Abstract: <i>Clonorchis sinensis</i> is the most common fish-borne intestinal parasite in Korea. The aim of the present investigation was to survey the status of <i>C. sinensis</i> infection and analyze associated risk factors in residents of Haman-gun, Gyeongsangnam-do. A total of 5,114 residents from 10 administrative towns/villages voluntarily agreed to participate in the study, which comprised fecal examination, a questionnaire survey for risk factors, ultrasonography, and enzymelinked immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…On one hand, both prevalence and infection intensity are considered in DALYs. Infection intensity indicates the worm burden [ 30 ], which is significantly related to the morbidity [ 11 , 31 ]. On the other hand, not only disability but also death are included in DALYs, which is very important because YLLs could also be caused in clonorchiasis due to cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, both prevalence and infection intensity are considered in DALYs. Infection intensity indicates the worm burden [ 30 ], which is significantly related to the morbidity [ 11 , 31 ]. On the other hand, not only disability but also death are included in DALYs, which is very important because YLLs could also be caused in clonorchiasis due to cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The different cost yield in different populations was essentially attributable to the difference in prevalence. Because clonorchiasis shows a significantly differential distribution in different genders and ages due to difference in ingesting raw freshwater fish [ 5 , 25 , 31 ]. Adult male shows a higher prevalence compared to adult female and both show higher prevalence compared to children.…”
Section: Discussionmentioning
confidence: 99%
“…The oriental liver fluke C. sinensis is currently the most important helminth in terms of prevalence and clinical significance. The endemicity of clonorchiasis has maintained at relatively high levels, especially in the riverside regions in Korea [ 1 – 7 ]. An epidemiological survey conducted from May 1979 to April 1980 reported a high prevalence of clonorchiasis in the riverside residents of 7 major rivers, such as Nakdong-gang (gang means river) (40.2%), Yeongsan-gang (30.8%), Seomjin-gang (17.3%), Tamjin-gang (15.9%), Han-gang (15.7%), Geum-gang (12.0%), and Mangyeong-gang (8.0%) [ 2 ].…”
Section: Background and Purposementioning
confidence: 99%
“…Approximately 932,540 people (1.9%) were estimated to be infected with C. sinensis . A recent study observed 5.3% prevalence of clonorchiasis in the residents of Haman-gun, Gyeongsangnam-do, which is located in the Nakdong-gang basin [ 7 ]. Although the endemicity of clonorchiasis is decreasing, this endemic trematodiasis still remains a major public health problem to be addressed in this country.…”
Section: Background and Purposementioning
confidence: 99%
“…In some areas, male infections were 2-3.6 times higher than female infections, which may be related to the different eating habits of men and women. In some areas, it was found that the number of men who have the habit of eating raw fish is three times that of women, and compared with women, men prefer to eat fish and have more social activities and eating opportunities[ 34 - 36 ]. With increasing age, the infection rates in both men and women increase, and infection exists in all age groups, with the highest infection rate in the age group of 50 to 59.…”
Section: Epidemiologymentioning
confidence: 99%